The Impact of Capital Structure on Corporate Profitability For Islamic Banks on Saudi Stock Exchange “Tadawul” - Alsaleh, Fatimah; Albarrak, Mohammed (The Arab Journal of Administration, 2024)
Compliance with Sharia governance has become an essential requirement for Islamic banks which can lead to several capital market consequences. In this study, we aim to examine the impact of bank’s capital structure on bank’s profitability for Saudi Islamic banks. The study uses a sample of several Islamic banks that are listed on the Saudi Stock Exchange for a sample period start from 2017 to 2021. Meanwhile, the findings of the study show insignificant association between capital structure measurements and return on assets (ROA) as a proxy for profitability. The study found that there is a significant negative association between bank’s capital structure (measured by total equity to total assets ratio) and corporate profitability (measured by Return on Equity: ROE). The study has also found that capital structure (measured by total liabilities to total assets ratio) is positively and statistically significantly associated with bank’s profitability (using Return on Equity as a proxy: ROE). The findings show that external and internal capital structure determinants have difference effects on banks’ profitability. Additionally, our results show that bank size has significant impact on corporate profitability for Saudi Islamic banks. The study provides several implications for banks’ managers, regulators and market participants.